2020
DOI: 10.1093/nar/gkaa1202
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage alters nuclear mechanics through chromatin reorganization

Abstract: DNA double-strand breaks drive genomic instability. However, it remains unknown how these processes may affect the biomechanical properties of the nucleus and what role nuclear mechanics play in DNA damage and repair efficiency. Here, we have used Atomic Force Microscopy to investigate nuclear mechanical changes, arising from externally induced DNA damage. We found that nuclear stiffness is significantly reduced after cisplatin treatment, as a consequence of DNA damage signalling. This softening was linked to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 61 publications
4
32
0
Order By: Relevance
“…The loss of heterochromatin at the nuclear rim and depletion of laminB2 in uhrf1 and dnmt1 mutants is a likely cause of the deformed nuclear shape, and we predict, result in reduced nuclear stiffness. Similar results linking chromatin state and nuclear morphology have been done mainly in cell lines [ 91 , 120 , 121 ], and our work establishes this link during hepatocyte development.…”
Section: Discussionsupporting
confidence: 90%
“…The loss of heterochromatin at the nuclear rim and depletion of laminB2 in uhrf1 and dnmt1 mutants is a likely cause of the deformed nuclear shape, and we predict, result in reduced nuclear stiffness. Similar results linking chromatin state and nuclear morphology have been done mainly in cell lines [ 91 , 120 , 121 ], and our work establishes this link during hepatocyte development.…”
Section: Discussionsupporting
confidence: 90%
“…Toseland et al reported that cisplatin-induced DNA damage is associated with cell stiffness. 46 The damage in the DNA caused by a DNA nick by HSNPc and detected by TUNEL staining ( Fig. 7 ) could affect the stiffness of HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
“…Toseland et al have reported that cisplatin-induced DNA damage is associated with cell stiffness. 46 The damage in the DNA caused by DNA nick by HSNPc and detected by Tunel staining (Figure 7) could affect the stiffness of HeLa cells. Cell biomechanics importantly regulates the function of the cells 47 , and stiffness is reported to alter the cell migration and invasion, which is particularly relevant for cancer metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously, the indentation of the sample is monitored by measuring the motion of the fixed end of the cantilever, thus enabling quantification of nuclear elasticity. This strategy has been used to elucidate how nuclear stiffness changes in response to, for example, chromatin compaction states, 65 DNA damage, 72 and altered lamin levels. 61 A unique degree of freedom with AFM is the shape of the tip at the free end of the cantilever.…”
Section: Methods In Nuclear Mechanobiologymentioning
confidence: 99%